Effects of the Novel NMDA Receptor Antagonist Gacyclidine on Recovery From Medial Frontal Cortex Contusion Injury in Rats - Jeffrey S. Smith; Zoltan L. Fulop; Steven A. Levinsohn; Richard S. Darrell; Donald G. Stein (Neural Plasticity)
Gacyclidine, a novel, noncompetitive NMDA receptor antagonist, was injected (i.v.) into rats at three different doses to determine if the drug could promote behavioral recovery and reduce the behavioral and anatomical impairments that occur after bilateral contusions of the medial frontal cortex (MFC). In the Morris water maze,contused rats treated with gacyciidine at a dosage of 0.1 mg/kg performed better than their vehicle-treated conspecifics. Rats given gacyclidine at either 0,3 or 0.03 mg/kg performed better than brain-injured controls, but not as well as those treated with 0.1 mg/kg. Counts of surviving neurons in the nucleus basalis magnoceilularis (NBM) and the medial dorsal nucleus (MDN) of the thalamus were used to determine whether gacyclidine treatment attenuated secondary cell death. In both the NBM and the MDN, the counts revealed fewer surviving neurons in untreated contused rats than in gacyclidine-treated rats. Increases in the size and number of microglia and astrocytes were observed in the striatum of gacyclidinetreated contused brains. Although most consequences of MFC contusions were attenuated, we still observed increases in ventricle dilation and thinning of the cortex. In fact, the ventricles of rats treated with 0.1 mg/kg of gacyclidine were larger than those of their vehicle treated counterparts, although we observed no behavioral impairment.